Orientation-tunable InxGa1−xN nanowires with a high density of basal stacking faults for photoelectrochemical/photocatalytic applications. Issue 12 (15th March 2021) - Yuan, Ronghuo; Luo, Qingyuan; Zhang, Zenghui; Zheng, Yufan; Feng, Dengtang; Wang, Defa; Hu, Yan-Ling
Abstract : In x Ga1− x N nanowires grew along the m -direction (A-NWs) or semipolar-direction (B-NWs) with the presence of a high density of BSFs. Abstract : In x Ga1− x N nanowires (NWs) have attracted much interest as promising photocatalysts. In this article, In x Ga1− x N nanowires were grown on an n-type Si (111) substrate by a Ni-catalyzed chemical vapor deposition (CVD) method. The preferred growth direction of the In x Ga1− x N NWs may be tuned through the position of metallic sources (gallium acetylacetonate and indium acetylacetonate) by affecting the composition of the Ni-based droplets. The metallic precursors at a higher temperature position led to straight and coarse NWs (A-NWs) with an In x Ga1− x N/GaN core/shell structure, which grew preferentially along the m -direction. In contrast, the metallic precursors at lower temperature positions resulted in curved and fine In x Ga1− x N NWs (B-NWs) mainly along semipolar directions. The A-NWs/Si electrode exhibited a higher photocurrent but the B-NWs/Si electrode showed a better photocatalytic performance in terms of H2 evolution and CO2 reduction upon irradiation. The different performances were attributed to the high density of basal stacking faults (BSFs), which can give rise to anisotropic transport of photogenerated electrons in NWs. The respective growth mechanism was analysed for the A- and B-NWs and a novel strategy was proposed to engineer the growth direction and BSFs in the In x Ga1− x N NWs.